2008
DOI: 10.1103/physrevb.78.104403
|View full text |Cite
|
Sign up to set email alerts
|

Interface alloying effects in the magnetic properties of Fe nanoislands capped with different materials

Abstract: We show that Fe nanoislands capped with Al, Pd, and Pt protecting layers include an alloy at the interface with the capping layer, which explains the previously known capping layer dependence on the interparticle magnetic coupling. Vibrating sample magnetometry results, for instance, are evidencing a reduction in the magnetization measured under a magnetic field of 15 mT, which is larger in the case of the Al capping and which is due to the presence of a magnetically dead interface alloy. This reduction is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The effect of the formation of an interface alloy between the Co and the Al deposits is enhanced for the thinnest Co deposits when compared to the reference sample as also observed in the case of Fe nanoparticles capped with Al. 35 On the other hand, there is an enhancement of the atomic orbital moment for both Pt and Al cappings. This quantity is very sensitive to small changes in the surface structure 36 and lowering the dimensionality is one of the main causes leading to an enhanced atomic orbital moment.…”
Section: B Atomic Magnetic Propertiesmentioning
confidence: 99%
“…The effect of the formation of an interface alloy between the Co and the Al deposits is enhanced for the thinnest Co deposits when compared to the reference sample as also observed in the case of Fe nanoparticles capped with Al. 35 On the other hand, there is an enhancement of the atomic orbital moment for both Pt and Al cappings. This quantity is very sensitive to small changes in the surface structure 36 and lowering the dimensionality is one of the main causes leading to an enhanced atomic orbital moment.…”
Section: B Atomic Magnetic Propertiesmentioning
confidence: 99%
“…On the other hand, in a recent study of the effect of interface alloying on magnetic properties of Fe capped with different HMs such as Pt and Pd, it was shown that in the Fe 2p 3/2 core level photoelectron spectrum, an additional peak, shifted toward a higher binding energy by about 1.5 eV, is observed. [ 32 ] This peak has been attributed to interfacial alloying of Fe with HMs. In the present case, the second peak is shifted by about 1.6 eV with respect to bcc Fe peak.…”
Section: Figurementioning
confidence: 99%
“…However, this may change the physical properties of the thin film. [4,5] Another solution is the installation of a small UHV chamber only dedicated to measurements at the instrument. [6] Consequently, a UHV transfer chamber is required for bridging the gap between the UHV preparation system and the measurement chamber.…”
Section: Introductionmentioning
confidence: 99%